Antimicrobial Activity of Marine Bacteria Isolated from the Mangalore Coast, West Coast of India - Boopalan, K. Gokulkrishnan, Kusuma. S and Kamala (Recent Research in Science and Technology, 2011)
Antibacterial substances from sea sediment were isolated from marine environment of Mangalore, west coast of India and characterized. Out of the 21 isolates subjected to secondary screening, 10 isolates were active against Bacillus subtilis, 12 against Staphylococcus aureus, 6 against Escherichia coli, 3 against Proteus vulgaris and 4 against Salmonella typhi. Metabolites in the extract of broth of overnight grown Pseudomonas spp. Ã‚Â No.MN05 proved to have antimicrobial activity.